What Are the Clinical Validation Requirements for AI in Healthcare? - Rasit Dinc (Rasit Dinc Digital Health & AI Research, 2022)
What Are the Clinical Validation Requirements for AI in Healthcare? The Regulatory Imperative for Trustworthy AI in Medicine The integration of Artifici...
Keywords: Drug Discovery; Digital Health; Diagnostics; Artificial Intelligence; Healthcare Innovation